Defective Cytochrome P450-Catalysed Drug Metabolism in Niemann-Pick Type C Disease - Platt, F; Nicoli, E; Al Eisa, N; Cluzeau, C; Wassif, C; Gray, J; Burket, K; Smith, D; Morris, L; Cologna, S; Peer, C; Sissung, T; et al. (Public Library of Science, 2016)
Niemann-Pick type C (NPC) disease is a neurodegenerative lysosomal storage disease caused by mutations in either the NPC1 or NPC2 gene. NPC is characterised by storage of multiple lipids in the late endosomal/lysosomal compartment, resulting in cellular and organ system dysfunction. The underlying molecular mechanisms that lead to the range of clinical presentations in NPC are not fully understood. While evaluating potential small molecule therapies in Npc1-/- mice, we observed a consistent pattern of toxicity associated with drugs metabolised by the cytochrome P450 system, suggesting a potential drug metabolism defect in NPC1 disease. Investigation of the P450 system in the context of NPC1 dysfunction revealed significant changes in the gene expression of many P450 associated genes across the full lifespan of Npc1-/- mice, decreased activity of cytochrome P450 reductase, and a global decrease of multiple cytochrome P450 catalysed dealkylation reactions. In vivo drug metabolism studies using a prototypic P450 metabolised drug, midazolam, confirmed dysfunction in drug clearance in the Npc1-/- mouse. Expression of the Phase II enzyme uridinediphosphate-glucuronosyltransferase (UGT) was also significantly reduced in Npc1-/- mice. Interestingly, reduced activity within the P450 system was also observed in heterozygous Npc1+/- mice. The reduced activity of P450 enzymes may be the result of bile acid deficiency/imbalance in Npc1-/- mice, as bile acid treatment significantly rescued P450 enzyme activity in Npc1-/- mice and has the potential to be an adjunctive therapy for NPC disease patients. The dysfunction in the cytochrome P450 system were recapitulated in the NPC1 feline model. Additionally, we present the first evidence that there are alterations in the P450 system in NPC1 patients.